Carabid (Coleoptera) community changes following prescribed burning and the potential use of carabids as indicators species to evaluate the effect of fire management in Mediterranean regions - Nunes, L. (2010)
Separata do Vol. 14, n.º da Revista Silva Lusitana.Pesquisável também em http://www.scielo.oces.mctes.pt/pdf/slu/v14n1/v14n1a07.pdf